Evaluation of the therapeutic use of antibiotics in Aegean Region hospitals of Turkey: A multicentric study - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2011)
Purpose: The antibiotic restriction policy has been validated nationwide since February 2003 by the Ministry of Health because the excessive consumption of antimicrobials causes a high cost. The aim of this study was to evaluate the therapeutic use of antibiotics in Aegean Region hospitals and to assess the impact of this nationwide antibiotic restriction policy. This new policy is based on justification that the infectious disease (ID) physicians should be primarily responsible for the prescription of antimicrobials. Materials and Methods: Eight university and government hospitals were included in the study. The criteria of the Council for Appropriate and Rational Antibiotic Therapy (CARAT) were considered. Both patient-based and antibiotic-based analyses were performed. For the analysis of inappropriate use, logistic regression was modeled. Results: Therapeutic use was determined in 540 patients by a total of 29 ID physicians. In the study, 30.2% of the patients were given antimicrobials and empirically started antibiotics accounted for 79% cases of therapeutic antibiotic use, and 60% of those were inappropriate (P = 0.001). The appropriate use of ID level antibiotics (P = 0.000) were very compatible with other antimicrobial groups. Conclusion: The study shows that the Turkish government's new intervention policy on antimicrobial prescribing has been effective.
Keywords: Antibiotic restriction policy; appropriate antibiotic usage; RESTRICTION POLICY; APPROPRIATE; CONSUMPTION